Principles of Network and System Administration - Mark Burgess (John Wiley & Sons Ltd, 2004)
Network and system administration is a branch of engineering that concerns the operational management of human–computer systems. It is unusual as an engineering discipline in that it addresses both the technology of computer systems and the users of the technology on an equal basis. It is about putting together a network of computers (workstations, PCs and supercomputers), getting them running and then keeping them running in spite of the activities of users who tend to cause the systems to fail. A system administrator works for users, so that they can use the system to produce work. However, a system administrator should not just cater for one or two selfish needs, but also work for the benefit of a whole community. Today, that community is a global community of machines and organizations, which spans every niche of human society and culture, thanks to the Internet. It is often a difficult balancing act to determine the best policy, which accounts for the different needs of everyone with a stake in a system. Once a computer is attached to the Internet, we have to consider the consequences of being directly connected to all the other computers in the world.